Early-Onset Neutropenia Induced by Rituximab in a Patient with Lupus Nephritis and Hemolytic Anemia - Mariangelí Arroyo-Ávila; Ruth M. Fred-Jiménez; Luis M. Vilá (Case Reports in Rheumatology)
Rituximab is an anti-CD20 monoclonal antibody that has been used to treat several complications of systemic lupus erythematosus (SLE) including nephritis, cerebritis, and hematological disorders. Neutropenia is among the adverse events associated with rituximab; this usually occurs several weeks after therapy. However, early-onset neutropenia has been reported only in a few cases. Herein, we describe a 36-year-old Hispanic SLE woman who developed severe early-onset neutropenia (0.3 × 109/L) after the second weekly rituximab infusion (375 mg/m2 weekly × 4) given for nephritis and hemolytic anemia. She also had early-onset thrombocytopenia after rituximab therapy. Both hematological disorders resolved 12 days after the fourth and final dose. This case, together with few others, suggests that early-onset neutropenia may occur during rituximab therapy. Even though rituximab-induced neutropenia seems to be transient, it may predispose SLE patients to severe complications such as infections.